Implementasi Pembelajaran Akhlak Berbasis Tarikh Sirah Nawabiyah Terhadap Pembentukan Karakter Siswa MAN 2 Banyumas - Yusriyah Yusriyah (UM Purwokerto Press, 2023)
Education is a means by which a person can shape his personality and behavior in order to gain spiritual strength, religion, intelligence, personality, noble character, self-control, and the skills needed to participate effectively in the life of society, nation and state. The importance of values in education cannot be overstated. Educators have the power to influence the behavior of their students, turning it from negative to positive in the eyes of society, religion, and other moral authorities. Sirah Nabawiyah contains deep teachings about moral education. Its contents include teachings that humans must always obey and comply with the commands of Allah SWT and stay away from his prohibitions; encourage good and prevent evil; defending the honor of Muslims and strengthening relations with Muslims; be kind, patient, forgiving, generous, courageous, etc.; and upholding the honor of Muslims and strengthening Muslim relations. The method in this study is a qualitative method with a descriptive approach.The values of moral education in studying Tarih Sirah Nabawiyah at MAN 2 Banyumas can be described as follows, based on the discussion and analysis of the data obtained above: a. The exemplary method, the habituation method, the lecture method, and the reward and punishment method are all used in teaching Tarih Sirah Nabawiyah to instill moral education values. b. Teacher supervision and muhasabah sheets help students learn the moral lessons of Tarih Sirah Nabawiyah, while mobile phones and unlimited time to go home hinder the process.